Local wisdom as a part of disaster communication: a study on the local storytelling in disaster mitigation - Fakhruddin, Irwan; Elmada, Maria Advenita Gita (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
Located between the tectonic plates of Asia and Australia, a zone of high tectonic activity on the Pacific Ring of Fire with a row of mountains and active volcanoes makes Indonesia one of the countries with the highest natural disaster risk in the world. One of the potential disasters that attract attention is the potential for megathrust in southern Java, which has the potential to cause a tsunami of up to 20 meters. Various disaster mitigation efforts were carried out, one of which was to explore disaster mitigation messages in local wisdom and rely on community leaders as bearers of mitigation messages. Using an exploratory case study method, this research seeks to see mitigation messages in local wisdom in Bayah, South Lebak. The role of community leaders is also observed in community-based disaster communication. As a result, it was found that many messages based on local wisdom had content on disaster mitigation and nature conservation. Community leaders have a strategic role as Key Opinion Leader in conveying disaster mitigation messages, both messages based on local wisdom and modern science, to the community.